ANALISIS KEKUATAN TARIK LOGAM PADUAN Al-Cu-Mg SEBAGAI DUDUKAN SHOCK ABSORBER SEPEDA MOTOR - Riri Sadiana; Deni Putra; Wahyu Hidayat (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2020)
Aluminum is a non-ferrous metal that has good thermal conductivity and is widely used in various mechanical machinery systems. Efforts to obtain additional mechanical strength from aluminum can be combined with Cu, Mg, Si, Mn, Ni and so on. This research was made to prepare a Motorcycle Shock Absorber that is useful as a pedestal and handle shock breakers against the swing arm, with aluminum alloy material (Al), copper (Cu), and magnesium (Mg). The purpose of this research is to know the tensile strength and know the value of the strain. The method of this research process is aluminum alloy with a variation of Specimen 1 ratio is 3% copper and 7% magnesium, for Specimen 2 replacement is 5% copper and 5% magnesium, and the variations that support Specimen 3 are 7% copper and 3% magnesium. From the results of this study, the tensile strength and strain values ​​obtained in specimen 1 were 125.5 MPa and 3.56%. For specimen 2 the tensile strength and strain values ​​were 150 Mpa and 3.42%. While the specimens of 100% tensile strength and strain are 137 Mpa and 7.48%. The best results from copper and magnesium alloys are Al alloys of 90%, Cu 5% and Mg 5%, with a tensile strength value of 150 MPa and a strain value of 3.42%.